ANALISIS DEBIT AIR ANDALAN PDAM DI DAERAH ZONA 5 WILAYAH SURABAYA BARAT PERTUMBUHAN PENDUDUK TAHUN 2028 - Saves, Faradlillah; Rochmah, Nurul; Putra, R. Firdaus Alamsyah (EXTRAPOLASI, 2020)
AbstractPDAM Surya Sembada Surabaya City is a regional company authorized to produce and distribute water to customers. Utilization is not only limited to household needs, but also for public facilities. Along with the growth of clean water, of course, it will increase as well. This Final Project will explain the calculation of the reliable discharge of PDAM Surya Sembada Surabaya City in the Zone 5 area of West Surabaya Region. It also analyzes population growth projections using the Arithmetic and Geometric methods and calculates water needs, so that the water needs of PDAMs in Zone 5 can be identified. West Surabaya Region in the next 10 years, namely in 2028. After knowing the reliable discharge and water needs of PDAMs in the Zone 5 area of West Surabaya Region, the water balance can be known. PDAM water demand in the Zone 5 region of West Surabaya Region in the next 10 years, namely in 2028, is 3,914.59 liters / second smaller than the current mainstay discharge based on data from PDAM Surya Sembada of Surabaya, which is 3,955.99 liters / second. This means that the mainstay discharge of PDAM water for customers in the Zone 5 region of West Surabaya Region is able to meet water needs until 2028. AbstrakPDAM Surya Sembada Kota Surabaya adalah perusahaan daerah yang berwenang untuk memproduksi dan mendistribusikan air kepada pelanggan. Pemanfaatannya tidak hanya terbatas untuk keperluan rumah tangga, tetapi untuk fasilitas umum juga. Seiring dengan pertumbuhan air bersih tentu saja akan semakin meningkat pula. Tugas Akhir ini akan menjelaskan perhitungan debit andalan PDAM Surya Sembada Kota Surabaya di daerah Zona 5 Wilayah Surabaya Barat. Selain itu juga menganalisa proyeksi pertumbuhan penduduk dengan menggunakan metode Aritmatik dan Geometrik serta menghitung kebutuhan air, sehingga dapat diketahui kebutuhan air PDAM di daerah Zona 5. Wilayah Surabaya Barat 10 tahun kedepan yaitu pada tahun 2028. Setelah diketahui debit andalan dan kebutuhan air PDAM di daerah Zona 5 Wilayah Surabaya Barat, maka dapat diketahui keseimbangan airnya. Kebutuhan air PDAM di daerah Zona 5 Wilayah Surabaya Barat 10 tahun kedepan yaitu pada tahun 2028 adalah 3.914,59 liter/detik lebih kecil dari debit andalan saat ini yang didasarkan dari data PDAM Surya Sembada Kota Surabaya yaitu sebesar 3.955,99 liter/detik. Artinya debit andalan air PDAM untuk pelanggan di daerah Zona 5 Wilayah Surabaya Barat mampu memenuhi kebutuhan air sampai tahun 2028.